2020
DOI: 10.1007/s40964-020-00117-7
|View full text |Cite
|
Sign up to set email alerts
|

Laser powder bed fusion of Nd–Fe–B permanent magnets

Abstract: In this work, we use laser powder bed fusion (LPBF) to produce Nd-Fe-B magnets. A suitable process window is developed, which allows to fabricate isotropic samples with outstanding magnetic performance. The sample quality is mainly defined by the energy input during LPBF and sintering or delamination occurs, if the process parameter are improperly adjusted. Magnetic and structural properties become better as energy input increases, until the material-specific limit for processability has been reached. Magnets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 23 publications
4
32
1
Order By: Relevance
“…The subsequent cooling process after liquefaction in general influences the grain size and the composition of the grain boundaries [ 31 ]. A direct comparison of the magnetic properties of our P-RE-8 printed sample with MQP-S printed samples in literature [ 13 , 18 , 19 ] reveals that the remanence is significantly larger for printed P-RE-8 ( J r = 0.69 T) compared to the printed MQP-S in literature (0.55–0.63 T), whereas the coercivity is significantly smaller for printed P-RE-8 ( µ 0 H c = 0.125 T) compared to the printed MQP-S in literature (factor 5–8). From this point of view, there is still potential to improve the magnetic properties of the printed P-RE-8 parts by optimizing the process parameters, including cooling conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The subsequent cooling process after liquefaction in general influences the grain size and the composition of the grain boundaries [ 31 ]. A direct comparison of the magnetic properties of our P-RE-8 printed sample with MQP-S printed samples in literature [ 13 , 18 , 19 ] reveals that the remanence is significantly larger for printed P-RE-8 ( J r = 0.69 T) compared to the printed MQP-S in literature (0.55–0.63 T), whereas the coercivity is significantly smaller for printed P-RE-8 ( µ 0 H c = 0.125 T) compared to the printed MQP-S in literature (factor 5–8). From this point of view, there is still potential to improve the magnetic properties of the printed P-RE-8 parts by optimizing the process parameters, including cooling conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to a significant deterioration of the hard magnetic properties [ 13 ] (in the case of laser directed energy process (LMD) a similar behavior has been observed [ 17 ]). Recently, it was demonstrated that fine-tuning the laser parameters may result in stabilization of the intended Fe 14 Nd 2 B phase with reduced (but still present) iron segregation for high cooling rates [ 13 , 18 , 19 , 20 ]. It turned out that a shallow laser melt pool (melt pool depth <50 µm) in general has to be considered favorable for rapid solidification and coercivities of up to 695 kA/m (0.87 T) [ 13 ] 825 kA/m (1.04 T) [ 18 ] and 886 kA/m (1.11 T) [ 19 ], respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it was recently shown for Fe-Nd-B, that rapid solidification in L-PBF can be realized. Precisely tuned processing parameters result in shallow melt pools, leading to nanocrystalline microstructures in the bulk showing hard magnetic properties [1][2][3][4][5]. One strategy is trying to realize microstructures by L-PBF processing that were previously only possible using powder metallurgy or rapid quenching.…”
Section: Introductionmentioning
confidence: 99%
“…It is historically also known as Selective Laser Melting (SLM), Laser Beam Melting (LBM), Direct Metal Laser Sintering (DMLS) and many other terms, most of them branded by OEM system manufacturers. LPBF of functional or smart materials includes magnetic materials, e.g., NdFeB [ 24 ], and Shape Memory Alloys, e.g., NiTi [ 25 , 26 ]. With LPBF having major advantages in the manufacturing of delicate, low-mass and small-sized components with superior mechanical properties at competitive prices compared to conventional manufacturing, a major strategy for LPBF application can be found within super lightweight lattice structures with excellent stiffness-to-weight ratio [ 27 ].…”
Section: Introductionmentioning
confidence: 99%